Issues about the work with text genres in the foreign language classroom: a discussion under the bakhtinian view - Aquino, Carla de (BELT - Brazilian English Language Teaching Journal, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->This article brings considerations on the importance of exploring text genres in the foreign language classroom as a tool to access different languages and social organizations. For doing so, we firstly present a brief review of the concept of genre for the Bakhtin Circle. Secondly, we come out with some considerations about the work with text genres in mother and foreign language, always with a reference to the National Curriculum Parameters for the third and fourth school cycles. The conception of language present in them and the one found in the work of the Circle are perfectly suitable. However, despite using genre to make up for the objectives of language teaching present in that document, the work still has not been systematized to the point of reaching classrooms and didactic materials.